Rotational Shortening of Collateral Ligament in TKR With Severe Deformity. Issue 4 (December 2018) - Ku, Ming-Chou; Hwang, Yiing-Feng; Cheng, Cheng-Kung; Chen, Jr-Kai; Kumar, Atul
Abstract : Instability of the knee joint after total knee replacement (TKR) is one of the most important reasons for revision TKR. Inadequate release or tightening of the collateral ligaments in the knee joint may cause instability and early failure. This study presents a case series study of a new technique for ligament balancing wherein the collateral ligament is detached from its origin and rotated (twisted) around its longitudinal axis to tighten the ligament before the origin is reattached to its original position. The surgical technique for collateral ligament tightening during TKR was performed on 6 patients with a deformed knee caused by osteoarthritis and rheumatoid arthritis. The range of motion, knee society score, and laxity of the patients' knee joint, after 7 months to 13 years of follow-up, were evaluated. The technique was successful, achieving good range of motion and satisfactory stability of the joint. Further evaluation in a larger number of cases and a comparative analysis with different techniques would further support the usefulness of this rotational ligamentoplasty technique.